2020
DOI: 10.1002/jcla.23493
|View full text |Cite
|
Sign up to set email alerts
|

The immunologic changes during different phases of intestinal anastomotic healing

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…Several mechanisms may explain the detrimental effect of intraoperative hypothermia on the healing of PJ anastomosis. First, intraoperative hypothermia suppresses the perioperative immune response required for proper intestinal anastomotic healing, 13,14 and a recent study has also reported that impairment of the immune response during the early postoperative period is associated with the occurrence of CR‐POPF 15 . Second, the immunologic impairment can promote microbial growth, 16 which could be an important contributing factor for gastrointestinal anastomotic leakage, including POPF 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may explain the detrimental effect of intraoperative hypothermia on the healing of PJ anastomosis. First, intraoperative hypothermia suppresses the perioperative immune response required for proper intestinal anastomotic healing, 13,14 and a recent study has also reported that impairment of the immune response during the early postoperative period is associated with the occurrence of CR‐POPF 15 . Second, the immunologic impairment can promote microbial growth, 16 which could be an important contributing factor for gastrointestinal anastomotic leakage, including POPF 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The 3D cell culture models or co-culture models would better mimic the interaction of cells that are relevant for intestinal wound healing. Thereby, not only fibroblast and IECs should be evaluated but also neutrophils and platelets, which are known to be involved in intestinal wound healing [22,56,57] and a potential target of Apremilast [58,59]. Besides cell differentiation and proliferation, angiogenesis plays a crucial part in intestinal wound healing [60].…”
Section: Positive Effects On Wound Healing In Vitro and Fibroblast Mi...mentioning
confidence: 99%